Accounting and financial analysis in the hospitality industry - Hales, Jonathan A. (Burlington, 2015)
"Accounting and Financial Analysis in the Hospitality Industry offers a clear introduction to fundamental accounting concepts and provides the tools to produce solid financial analysis and optimal operational performance in hotels and restaurants. The text examines the current practices of some of today's leading hotel and restaurant companies and introduces the fundamentals of hospitality accounting from a practical, applied perspective with real industry examples." "In addition, Accounting and Financial Analysis in the Hospitality Industry provides hospitality managers the knowledge and experience to be comfortable working with the numbers to manage their departments effectively. This insight will equip managers with the skills needed to perform efficiently and correctly in all their accounting and financial roles including revenue forecasting, wage scheduling, budgeting, P & L critiques, purchasing procedures and cost control methods."